Updating the soil mapping of the State of Mexico: a planning tool - Sotelo Ruiz, Erasto Domingo; González Hernández, Antonio; Cruz Bello, Gustavo; Flores López, Román (Revista Mexicana de Ciencias Agrícolas, 2020)
The soil is a very important natural body for the development of crops and plant species, because it provides support to the roots of plants, it also provides nutrients for their development and production, depending on the type of soil and its properties. Knowing and quantifying soils is necessary to plan agricultural, livestock, forestry, urban, mining and conservation activities. The objectives of this work were: 1) to update the 1:50 000 soil mapping per municipality in the State of Mexico; and 2) quantify the surface of the soils and know their location to identify areas of productive reconversion. The cartography was generated with the digitization of the 1:50 000 scale soil charts, with a geographic information system (GIS), its database was generated: primary soils, secondary soils, physical phase, chemical phase and texture; this database was updated to the 2015 WRB soils version. The soils with the largest and most productive areas are: Andosols with 479 908 ha, Pheozems with 472 718 ha, Vertisols with 241 485 ha and Cambisols with 196 047 ha. These predominate in the municipalities of Aculco, Toluca, Acambay, Jilotepec, Axapusco, Ixtlahuaca and Almoloya de Juárez.
Keywords: digital cartography; municipality; soils; update